Volcanic and sedimentary facies of the Huka Group arc-basin sequence, Wairakei–Tauhara Geothermal Field, New Zealand. Issue 2 (2nd April 2016) - Cattell, HJ; Cole, JW; Oze, C
ABSTRACT: Detailed facies analyses of intra-arc basin stratigraphy provide spatial and temporal insights into the nature and timing of past volcanic, sedimentary and tectonic events. Rift and caldera basins hosting lakes in the central Taupo Volcanic Zone (TVZ) continental arc preserve a sequence of locally and regionally sourced volcanic deposits and interbedded lacustrine sediments. A series of new continuous core samples from Wairakei–Tauhara Geothermal Fields in the TVZ intersecting thick Huka Group stratigraphy has provided a unique opportunity to study c. 300 ka of local arc volcanism, sedimentary processes and ancient surface environments. Facies analysis is utilised on 11 cored wells from across Wairakei–Tauhara, including a newly defined Huka Group Reference Section well (WKM15). Interpreted facies identify that the Huka Group commenced with a large ignimbrite (Waiora Ignimbrite Member) emplaced onto faulted relief covered by a pre-existing ancient lake, Lake Huka. Graded volcaniclastic facies, lavas and sediments comprising the Waiora Volcaniclastics Member then accumulated in the basins over the next c. 100 ka. A spatially variable switch from volcaniclastic (Waiora Volcaniclastics Member) to lacustrine siltstones and sandstones (Huka Falls Formation) deposition then followed in Lake Huka. Excluding an intra-lake phreatomagmatic eruption (Middle Huka Falls Formation), these lacustrine sediments reflect a c. 200 ka local pyroclastic hiatus. Late Huka Group deposition became gradually more fluvial as rivers prograded marginal areas of the lake until its destruction by the 25.4 ka Oruanui eruption. The drill core samples provide new complete and detailed insights into processes and environments associated with the Huka Group. These enhance our understanding of the geological history at Wairakei–Tauhara Geothermal Fields and contribute to our knowledge of the ancient processes that occurred during evolution of the TVZ.